Norm and form. The “window” element as an example of revision of Turin’s regulatory system - Marianna Nigra; Caterina Barioglio; Daniele Campobenedetto (Techne)
The objective of this paper is to explore the role of urban codes in the transformation processes of the ordinary city. By focusing on the case study of the City of Turin, the article investigates the relationship between the regulatory system and urban form through the “window” element, providing suggestions for acting on building planning and regulation tools. In particular, the object of the research is the set of rules relating to the performance of buildings with respect to the supply of daylight and its implementation with the environmental regulation system. The paper proposes an integration to the Building Regulations, with the aim of reorienting the use of rules both as control tools during the project (and not exclusively as ex post verification), and as devices capable of enabling ordinary transformations of the city.